Responsabilidade social empresarial no campo das corretoras de seguros brasileiras - Guimarães, Jairo de Carvalho (2009)
Taking the theme of Corporate Social Responsibility (CSR), this study was developed in the Brazilian segment of the insurance brokerage that represents significant role in the economy. In the theoretical framework, the Ethos Indicators (ETHOS, 2007) are used as a parameter. Similarly, field research was conducted in four insurance brokers listed in the Ethos Institute of Business and Social Responsibility, based in 2007. The objective of this research is to investigate the stage of development of indicators related to the themes Values, Transparency and Governance and Internal Public, which are part of the list of seven topics of the questionnaire of the Ethos Institute. The cut made reflects the relevance of these themes and their subthemes for the field in focus. This is a descriptive-exploratory research, conducted through a survey. As for the results, it appears that although there is some concern to deepen the practice of CSR, they are, in general, still in early stages, requiring, therefore, a commitment of companies towards more effective actions. Of the two issues addressed, there is concentration of actions in the Internal Public, through conduct targeted in relations with officials, as seen in indicators related to the subtheme decent work. Despite the complexity of the activity and the ethical underpinning to it, because it relies on a relationship of trust, the insurance brokers show reluctance in terms of socially responsible practices, which indicates a lack of awareness of the importance of this theme in their field of expertise. Because of the broad horizon that represents the subject in the dynamic economy, future studies may contribute to the further deepening of the subject in the activity of insurance brokerage, encouraging other companies to join the CSR movement, enabling a new social reality to arise in the segment.